Genome-wide copy number variation analysis identifies novel candidate loci associated with pediatric obesity. (November 2018) - Selvanayagam, Thanuja; Walker, Susan; Gazzellone, Matthew; Kellam, Barbara; Cytrynbaum, Cheryl; Stavropoulos, Dimitri; Li, Ping; Birken, Catherine; Hamilton, Jill; Weksberg, Rosanna; Scherer, Stephen
Abstract Obesity is a multifactorial condition that is highly heritable. There have been 60 susceptibility loci identified, but they only account for a fraction of cases. As copy number variations (CNVs) have been implicated in the etiology of a multitude of human disorders including obesity, here, we investigated the contribution of rare (<1% population frequency) CNVs in pediatric cases of obesity. We genotyped 67 such individuals, including 22 with co-morbid developmental delay and prioritized rare CNVs at known obesity-associated loci, as well as, those impacting genes involved in energy homeostasis or related processes. We identified clinically relevant or potentially clinically relevant CNVs in 15% (10/67) of individuals. Of these, 4% (3/67) had 16p11.2 microdeletions encompassing the known obesity risk geneSH2B1 . Notably, we identified two unrelated probands harboring different 6p22.2 microduplications encompassingSCGN, a potential novel candidate gene for obesity. Further, we identified other biologically relevant candidate genes for pediatric obesity includingARID5B, GPR39, PTPRN2, andHNF4G . We found previously reported candidate loci for obesity, and new ones, suggesting CNV analysis may assist in the diagnosis of pediatric obesity.